Identification of a major quantitative trait locus underlying salt tolerance in ‘Jidou 12’ soybean cultivar - XiaoLei Shi; Long Yan; ChunYan Yang; WeiWen Yan; David Octor Moseley; Tao Wang; BingQiang Liu; Rui Di; PengYin Chen; MengChen Zhang (BMC Research Notes, 2018)
Abstract Background Identification of the quantitative trait locus (QTL) underlying salt tolerance is a prerequisite for marker-assisted selection in the salt-tolerant breeding process. Methods In this study, the recombinant inbred lines derived from the salt-tolerant elite soybean cultivar ‘Jidou 12’ and the salt-sensitive elite cultivar ‘Ji NF 58’ were used to identify the QTL associated with salt tolerance, using both salt tolerance rating (STR) and leaf chlorophyll content (SPAD) as indicators. Results A major salt-tolerant QTL, which was flanked by SSR markers GMABAB and Barcsoyssr_03_1421 on chromosome 3, was identified based on single-marker regression, single trait composite interval mapping, and multiple interval mapping analysis. For STR, the LOD ranged from 19.8 to 20.1; R2 ranged from 44.3 to 44.7%; and the additive effect ranged from 0.876 to 0.885 among the three mapping methods. For SPAD, the LOD ranged from 10.6 to 11.0; R2 ranged from 27.0 to 27.6%; and the additive effect ranged from 1.634 to 1.679 among the three mapping methods. Conclusions In this study, a major QTL conditioning salt tolerance on chromosome 3 was identified. The DNA markers closely associated with the QTLs might be useful in marker-assisted selection for soybean salt tolerance improvement in Huanghuaihai, China.